Marx's analysis and the present day crisis. (26th July 2011) - Callinicos, Alex
This paper sketches Marx's method and then asks how it must be developed to explain the peculiarities of the present day crisis. It reviews some of the ways in which capitalism has changed in recent decades and argues that financialisation developed as a response to a protracted crisis of accumulation and profitability. The bursting of the bubble in 2007-2008 and subsequent crisis show the limits of the bubble driven boom but the political forces of neo-liberalism are determining the austerity drive in the advanced world. It is not clear that, even in its own terms, generalised austerity is a coherent economic response to a generalised crisis.